2022
DOI: 10.3390/ijerph19020829
|View full text |Cite
|
Sign up to set email alerts
|

A Descriptive Cohort of Suicidal Cancer Patients: Analysis of the Autopsy Case Series from 1993 to 2019 in Milan (Italy)

Abstract: Suicide in cancer patients has always been a subject of clinical studies, but the contribution of forensic pathology to this phenomenon is poorly reported. With the aim of at least partially filling this gap in information, at the Institute of Forensic Medicine of Milan, Italy, we assessed all suicides that occurred in cancer patients. A descriptive and retrospective analysis was carried out by examining the database of the Institute and autopsy reports. We included 288 suicide cases with proven cancer disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Interestingly, some studies have shown that the presence of multiple mental disorders should be deepen as a risk factor both in the general population (Rockett et al, 2007) and in psychiatric patients (Nock et al, 2010). However, among organic diseases cancer is prevalent in suicide (Gentile et al, 2022). Considering the administered pharmacological treatments, as expected, psychiatric inpatients were mainly treated with psychotropic medications whereas non‐psychiatric inpatients with non‐psychotropic medications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, some studies have shown that the presence of multiple mental disorders should be deepen as a risk factor both in the general population (Rockett et al, 2007) and in psychiatric patients (Nock et al, 2010). However, among organic diseases cancer is prevalent in suicide (Gentile et al, 2022). Considering the administered pharmacological treatments, as expected, psychiatric inpatients were mainly treated with psychotropic medications whereas non‐psychiatric inpatients with non‐psychotropic medications.…”
Section: Discussionmentioning
confidence: 99%
“…Considering non‐psychiatric inpatients, cancer patients are among the most affected by suicide. The current sub‐sample of oncological inpatients ( N = 24) has already been included in a recent study (Calati et al, 2021; Gentile et al, 2022). Drug therapies have been grouped in psychotropic drugs, such as antidepressants, anxiolytics, benzodiazepines, and sedatives, and non‐psychotropic drugs, such as chemotherapeutics, cardiotonics, antiretrovirals, and antihypertensives.…”
Section: Methodsmentioning
confidence: 99%